Correlation of Risk Factors with The Incidence Of Functional Dyspepsia Syndrome in Medical Faculty Students, Universitas Khairun - Muhammad S.F. Syah; Abdul A. Manaf; Fera The (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2022)
Background: Dyspepsia is a collection of discomfort, epigastric pain, bloating, nausea, vomiting, belching and a feeling of fullness. Stress, diet, irritating food/drink, non-steroidal anti-inflammatory drugs, Helicobacter pylori bacteria, alcohol and smoking are risk factors for dyspepsia. Although it is ranked 8th out of 10 specific diseases in North Maluku, there has been no research regarding the association of risk factors with incidence in this group, especially in young people at Khairun University. Purpose: Knowing the relationship of risk factors with the incidence of functional dyspepsia syndrome in students of the Faculty of Medicine Khairun University. Methods: Observational and analytic case control study with Total Ramdom Sampling at Medical Faculty students 2018-2021.Results: In 136 samples, a statistically significant relationship (<0.05) was found between gender, stress level, consumption of irritating food or drink, consumption of non-steroidal anti-inflammatory drugs, smoking degree and the incidence of functional dyspepsia syndrome in students of the Faculty of Medicine, Khairun University, while diet and alcohol consumption did not have a significant relationship. Conclusion: Most of the risk factors affected the incidence of functional dyspepsia syndrome in students of the Faculty of Medicine, Universitas Khairun.